Analysis And Database Design from Import And Export Reporting in Company in Indonesia - Novan Zulkarnain (Bina Nusantara University, 2016)
Director General of Customs and Excise (DJBC) is a government agency that oversees exports and imports in Indonesia. Companies that receive exemption and tax returns are required to wipe Orkan activities export and import by using IT-based reporting. This study aimed to analyze and design databases to support the reporting of customs based report format for Director General of Customs and Excise No. PER-09/BC/2014. Data collection used was the Fact Finding Techniques consisted of studying the documents, interviews, observation, and literature study. The methods used for Design Database System is DB-SDLC (System Development Life Cycle Database), namely: Conceptual Design, Design Logical and Physical Design. The result obtained is ERD (Entity Relationship Diagram) that can be used in the development of Customs Reporting System in companies throughout Indonesia. In conclusions, ERD has been able to meet all the reporting elements of customs.